(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the types of artistic imagery and poetic devices employed in Kaʿb ibn Zuhayr’s qasida “Baanat Suʿad,” regarded as one of the earliest masterpieces of Islamic literature. The study highlights the poet’s mastery in utilizing artistic techniques such as simile (tashbih), metaphor (istiʿara), allegory, and irony, and examines their semantic and phonological dimensions. The analysis further explores the harmony between Pre-Islamic (Jahiliyya) poetic traditions and the Islamic spirit manifest in the literary devices of the qasida, with particular attention to the descriptions of Suʿad, the garobil (sieve) simile and its phonological significance, and the rhetorical device of tajrid (abstraction).